Innate PI3K p110δ Regulates Th1/Th17 Development and Microbiota-Dependent Colitis - Steinbach, Erin C; Kobayashi, Taku; Russo, Steven M; Sheikh, Shehzad Z; Gipson, Gregory R; Kennedy, Samantha T; Uno, Jennifer K; Mishima, Yoshiyuki; Borst, Luke B; Liu, Bo; Herfarth, Hans; Ting, Jenny P Y; et al. (The Journal of immunology (1950), 2014)
The p110δ subunit of class IA PI3K modulates signaling in innate immune cells. We previously demonstrated that mice harboring a kinase-dead p110δ subunit (p110δKD) develop spontaneous colitis. Macrophages contributed to the Th1/Th17 cytokine bias in p110δKD mice through increased IL-12 and IL-23 expression. In this study, we show that the enteric microbiota is required for colitis development in germfree p110δKD mice. Colonic tissue and macrophages from p110δKD mice produce significantly less IL-10 compared with wild-type mice. p110δKD APCs cocultured with naive CD4+ Ag-specific T cells also produce significantly less IL-10 and induce more IFN-γ– and IL-17A–producing CD4+ T cells compared with wild-type APCs. Illustrating the importance of APC–T cell interactions in colitis pathogenesis in vivo, Rag1−/−/p110δKD mice develop mild colonic inflammation and produced more colonic IL-12p40 compared with Rag1−/− mice. However, CD4+CD45RBhigh/low T cell Rag1−/−/p110δKD recipient mice develop severe colitis with increased percentages of IFN-γ– and IL-17A–producing lamina propria CD3+CD4+ T cells compared with Rag1−/− recipient mice. Intestinal tissue samples from patients with Crohn’s disease reveal significantly lower expression of PIK3CD compared with intestinal samples from non–inflammatory bowel disease control subjects (p < 0.05). PIK3CD expression inversely correlates with the ratio of IL12B:IL10 expression. In conclusion, the PI3K subunit p110δ controls homeostatic APC–T cell interactions by altering the balance between IL-10 and IL-12/23. Defects in p110δ expression and/or function may underlie the pathogenesis of human inflammatory bowel disease and lead to new therapeutic strategies.